2015
DOI: 10.1002/alr.21519
|View full text |Cite
|
Sign up to set email alerts
|

Nasal lavage levels of granulocyte‐macrophage colony‐stimulating factor and chronic nasal hypereosinophilia

Abstract: Our data confirm that GM-CSF is more frequently detectable in nasal lavages of patients affected by chronic sinonasal eosinophilic inflammation than in controls. Statistical analyses revealed a significant weakly-moderate correlation between GM-CSF levels in nasal lavage of all patients and percentage of eosinophil infiltration of nasal mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…Several authors have tried to distinguish nasal polyp (NP) patients based on predominant inflammatory cell type/cytokine expression; the most common classification differentiates them into eosinophilic CRSwNP and non‐eosinophilic CRSwNP . In Western countries, CRSwNP is mostly characterized by eosinophilic inflammation with a prevalence ranging between 70% and 90% according to different reports .…”
mentioning
confidence: 99%
“…Several authors have tried to distinguish nasal polyp (NP) patients based on predominant inflammatory cell type/cytokine expression; the most common classification differentiates them into eosinophilic CRSwNP and non‐eosinophilic CRSwNP . In Western countries, CRSwNP is mostly characterized by eosinophilic inflammation with a prevalence ranging between 70% and 90% according to different reports .…”
mentioning
confidence: 99%
“…The pathogenesis of chronic hypereosinophilia in nasal mucosa is not well known. Recent findings indicated an increased transendothelial migration of eosinophils, attracted and activated by chemokines and cytokines . Eotaxin‐1 (CCL11), eotaxin‐2 (CCL24), and eotaxin‐3 (CCL26) seem to be potent and selective attractants .…”
mentioning
confidence: 99%
“…In our review of the literature, we found only one recently published study concerning the association between GM-CSF levels in nasal secretions and nasal eosinophilia. De Corso et al 21 found detectable levels of this cytokine in 34 of 70 (48.57%) patients, with an average concentration of 2.67 ± 0.8 pg/ml, whereas, only 1 out of 20 individuals in the control group showed detectable GM-CSF levels. In our study, we found detectable levels of GM-CSF in 22 of 28 patients (71.57%).…”
Section: Discussionmentioning
confidence: 95%